Analyzing the Impact of Leadership, School Culture, Organizational Communication, and Academic Supervision on Teacher Performance - M. Amin; Tien Rafida; Muhammad Rifai; Anan Nisoh (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze the influence of leadership, school culture, organizational communication, and academic supervision on improving teacher performance in schools, with academic supervision as an intervening variable. This study uses a quantitative approach through survey methods and path analysis techniques. The results of the study indicate that leadership has a direct effect on academic supervision (6.1%), school culture (9.7%), and organizational communication (3.0%). Furthermore, leadership has a direct effect on teacher performance (16.8%), school culture (6.2%), organizational communication (9.0%), and academic supervision (8.1%). The indirect effect through academic supervision is relatively small, namely leadership by 2.1%, school culture by 2.2%, and organizational communication by 1.5%. This indicates that the role of academic supervision as a mediating variable is still weak. Simultaneously, leadership, school culture, organizational communication, and academic supervision account for 56.5% of improvements in teacher performance, while other factors outside the research model account for 43.5%. Based on these findings, this study develops a new conceptual model, namely the Direct Influence Dominance-Based Teacher Performance Model (MKG-DPL), which confirms that improvements in teacher performance are more strongly influenced by direct strengthening of organizational variables than by mediation mechanisms.